Preventive Maintenance Motor Listrik 380 V pada Penggerak System Belt Conveyor Di PT Indonesia Power PLTU Banten 2 Labuan Omu - Irwan Syah; Ilham Akbar Darmawan (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
With the development of science and technology, the need for energy is getting bigger. influenced by an increase in population and human needs. One example of energy needed by all parties, including industries, is electrical energy. Electrical energy is an energy that cannot be separated from everyday life, where almost all equipment uses electrical energy both in industry and in development itself which is one of the factors that demand the supply of electrical energy. One of the most important equipment in the PLTU, namely the drive on the conveyor belt, is a 380 V electric motor. Electric motors are prone to being overloaded because they are used too often to reach the target, and also because these electric motors are often exposed to dust from coal which can cause the electric motor to accumulate dirt in the electric motor where the electric motor becomes obstructed and when it reaches letting it sit continuously can make the electric motor not optimal in operation and can be totally damaged.